PERAN KEPALA SEKOLAH DAN PENGAWAS DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DI PONDOK PESANTREN IMAM AN NAWAWI PEKANBARU - Muawiyah; An An Andari; Toha Ma'arif (UNISAN JURNAL, 2025)
The purpose of this study was to determine the role of school principals and PAI supervisors in improving student achievement. This research is a qualitative research. Sources of research data are primary and secondary data sources. Data collection methods are through interviews, observation and documentation. The steps taken in data analysis are data reduction, data presentation and verification or drawing conclusions. The results of the research data analysis show that the role of the school principal in improving student learning achievement at Pondok Pesantren Imam An Nawawi Pekanbaru is as a coordinator, as a consultant, as a leader, and as an evaluator. Meanwhile, the role of PAI supervisors in improving student learning achievement is as a partner, as a supervisor, as a coach and as a motivator. The learning achievement of students at Pondok Pesantren Imam An Nawawi Pekanbaru with the role of the school principal and supervisor of Islamic religious education (PAI) has increased. And student learning achievement can be seen based on learning achievement in the cognitive, psychomotor and affective aspects of students contained in daily test scores, midterm exam scores (UTS), fin